2020
DOI: 10.1016/s2468-1253(20)30007-8
|View full text |Cite
|
Sign up to set email alerts
|

The global, regional, and national burden of oesophageal cancer and its attributable risk factors in 195 countries and territories, 1990–2017: a systematic analysis for the Global Burden of Disease Study 2017

Abstract: Background Oesophageal cancer is a common and often fatal cancer that has two main histological subtypes: oesophageal squamous cell carcinoma and oesophageal adenocarcinoma. Updated statistics on the incidence and mortality of oesophageal cancer, and on the disability-adjusted life-years (DALYs) caused by the disease, can assist policy makers in allocating resources for prevention, treatment, and care of oesophageal cancer. We report the latest estimates of these statistics for 195 countries and territories be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
181
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(210 citation statements)
references
References 56 publications
4
181
0
1
Order By: Relevance
“…Our results showed the highest disease burden of esophageal cancer in Eastern Asia, Eastern Africa, South Africa, and Northern Europe, and lower burden in Central America, Western Africa, Northern Africa, and Western Asia. These findings are generally consistent with those of a GBD study for esophageal cancer in 2017, although there was a slight difference in the order (Eastern Asia, South Africa, and Eastern Africa) [ 18 ]. This may be caused by the different time frames, data sources, and methods of modelling used for the estimation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results showed the highest disease burden of esophageal cancer in Eastern Asia, Eastern Africa, South Africa, and Northern Europe, and lower burden in Central America, Western Africa, Northern Africa, and Western Asia. These findings are generally consistent with those of a GBD study for esophageal cancer in 2017, although there was a slight difference in the order (Eastern Asia, South Africa, and Eastern Africa) [ 18 ]. This may be caused by the different time frames, data sources, and methods of modelling used for the estimation.…”
Section: Discussionsupporting
confidence: 90%
“…We previously found that there was an inverse association between the incidence of SCC and level of GDP and HDI at the country level [ 5 ]. The substantial reduction in the incidence of SCC in many less developed regions might be attributed to the decreased prevalence of risk factors associated with improving socioeconomic status [ 5 , 18 ]. Although the prognosis of esophageal cancer remains poor, the general decrease in mortality may, at least to some extent, be explained by the advancement of diagnostic technology and treatment, such as detection and treatment for early-stage esophageal cancer by upper endoscopy, neoadjuvant chemotherapy, and minimally invasive esophagectomy [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ongoing increasing incidence of esophageal adenocarcinoma (EAC) and its still dismal prognosis in most patients has stimulated interest in its early detection ( 1 ). Although Barrett's esophagus (BE) is a known precursor of EAC, only a minority of patients with EAC are known with a previous diagnosis of BE ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 More than 85% of all EC cases were diagnosed with esophageal squamous cell carcinoma (ESCC) . 3 Despite advancement in therapeutic strategies have improved the prognosis of ESCC patients, the long-term survival still remains dismal. 4 As we all know, TNM staging system has been correlated with survival in predicting prognosis for ESCC.…”
Section: Introductionmentioning
confidence: 99%